Study of summer overheating on the new masonry self-insulating block (2019)
It seems that brick manufacturers in Slovakia are well prepared for high thermal resistance requirements. However, they are not ready for the requirement of the summer overheating that occurs more frequently. The article deals with a new type of asymmetric masonry block in various variants of its possible construction. The primary goal is to improve the thermal comfort in summer and eliminate the overheating. The new type of ceramic block is based on an existing mineral-filled block and it is supplemented with an internal thermal storage layer. The dynamic simulations presented in the paper show how the resulting indoor temperature could be lowered when the brick is properly adjusted. It also shows how the most popular wall is currently 300 mm thick aerated concrete with 150 mm thick polystyrene. They are practically on the same level. An improvement of approximately 0.8 ° C may come with the use of new special types of bricks aimed at combating summer overheating.